Light-response self-degradation ultra-small mesoporous organosilicon drug delivery system as well as preparation method and application thereof
By introducing the SE-SE bridge and photoretimension in the introduction of the SE-SE bridge and photomineromic agent in the medium nanoparticles to form an ultra-small medium-sized silicon drug delivery system that responds to self-degradable, it solves the toxic problem caused by the long degradation time of nanoparticles. Fast biodegradation and efficient treatment effect.
Patent Information
- Application Number
- CN202310886415.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
AI Technical Summary
The degradation time of existing mesoporous silica nanoparticles in biological organisms is long, resulting in the accumulation of nanoparticles, triggering long-term toxicity, and limiting their clinical application.
By introducing organic bonds, especially Se-Se bridges, into the inorganic silicon framework, the biodegradation rate of the material is improved, and photosensitizers are connected in the framework of silicon nanomaterials to achieve light-responsive self-degradation of ultra-small mesoporous organic silicon delivery Preparation of drug systems.
It achieves rapid biodegradation of nanomaterials, avoids accumulation in the body, improves the biocompatibility and therapeutic effect of the material, and releases drugs on demand through photodynamic therapy.
Smart Images

Figure CN119326909A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new medicinal materials and relates to a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system and a preparation method and application thereof. Background Art
[0002] The application of silicon nanomaterials in the biomedical field has been widely studied. Compared with other nanocarriers, mesoporous silica nanoparticles (MSNs) have the advantages of high surface area, good stability and biocompatibility, and are a nanocarrier material with great clinical application prospects. Mesoporous silica nanoparticles can deliver different substances to target locations in the body by performing different functional modifications on the surface of the nanoparticles. These substances may include small drug molecules and biological macromolecules such as proteins. Although the research on MSNs is developing rapidly, there is still no nanocarrier based on this material that has entered the stage of clinical application. The reason for this is that it takes a considerable amount of time for MSNs to degrade in the environment of the body, which will cause silicon nanoparticles to accumulate in the body, leading to long-term toxicity. In order to overcome these shortcomings, some studies tend to introduce organic bonds into the inorganic framework of MSNs. The more commonly used chemical bonds are SS and Se-Se. These two bonds have been widely proven to be highly active under physiological conditions, especially in the microenvironment of tumors, thereby effectively improving the biodegradation rate of materials in the body. At present, studies have shown that drugs encapsulated in Se-Se bridged mesoporous silica are more likely to be released under redox conditions than SS bridged mesoporous silica. In addition, there are a large number of literature reports that Se-Se has ROS response. In addition, studies have shown that ultra-small silicon nanomaterials with a size of less than 20nm have good tumor targeting and biocompatibility, and can also be quickly cleared and do not accumulate in the body. In addition, ultra-small silicon nanomaterials Cornell dots have been applied to the clinical stage, indicating that ultra-small silicon nanomaterials have great prospects for clinical transformation.
[0003] Tumor microenvironment (TME) refers to the local steady-state environment composed of tumor cells and non-tumor cells during the growth, occurrence and metastasis of tumors. Due to the excessive proliferation of cancer cells, tumor tissues have abnormal metabolism, so compared with normal tissues, the tumor microenvironment has acidic and redox characteristics. A large number of studies have shown that some carcinogens can produce aerobic metabolites such as hydrogen peroxide and hydroxyl radicals. These substances are collectively referred to as reactive oxygen species, which leads to higher than normal ROS levels in tumor tissues. In addition, during environmental stress (for example, ultraviolet or heat exposure), ROS levels will increase sharply, which may cause serious damage to cell structure and cause cell apoptosis. In addition, the abnormal metabolism of tumor tissues also causes tumor tissues to have strong reducing properties. Among them, glutathione (GSH) is a common reducing substance in tumor tissues. The concentration of GSH in tumor cells is much higher than that outside the cells. The concentration of GSH in tumor cells can reach 2-10mmol / L, while the concentration outside the cells is only 2-20μmol / L. The difference in GSH concentration between normal tissues and tumor tissues is also large. In some drug-resistant tumor cells, this difference can reach 10 times.
[0004] Photodynamic therapy (PDT) refers to a treatment method in which photosensitizers are activated and kill cells under the condition of laser light. Its specific mechanism of action is that after the photosensitizers accumulate at the treatment site, they are excited by irradiation with a specific laser wavelength. The energy generated is transferred to the oxygen in the tissue environment to produce reactive oxygen species (ROS). Excessive ROS levels can lead to oxidation of mitochondrial / nuclear DNA, proteins and other substances in the cells, causing oxidative damage, inducing cell apoptosis and ultimately leading to cell death. Reactive oxygen species broadly refer to oxygen-derived free radicals and non-free radicals, including superoxide anions (O 2- ), hydrogen peroxide (H 2 O 2 ), hydroxyl radical (OH - ), ozone (O 3 ) and singlet oxygen ( 1 O 2 ). Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system in view of the above-mentioned deficiencies in the prior art.
[0006] Another object of the present invention is to provide a light-responsive self-degrading ultra-small mesoporous organosilicon drug delivery system prepared by the above method.
[0007] Another object of the present invention is to provide an application of the light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system.
[0008] The purpose of the present invention can be achieved through the following solutions:
[0009] A method for preparing a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system comprises the following steps:
[0010] (1) Preparation of silanized photosensitizer:
[0011] A photosensitizer with a carboxyl group undergoes an amidation reaction with a silane coupling agent in the presence of an amide condensation agent to obtain a silanized photosensitizer;
[0012] (2) Preparation of biodegradable ultra-small silicon nanomaterials for photodynamic therapy:
[0013] In an alkaline environment, in the presence of a directing agent, the inorganic silicon source, the organic silicon source and the silanized photosensitizer prepared in step (1) are hydrolyzed and cross-linked to form silicon-oxygen bonds, gradually forming silicon spheres, and PEG chains are modified on the surface thereof to increase the stability of the preparation. The reaction solution is dialyzed with an acidic solution and water, and filtered with a 0.22 μm filter membrane to obtain a clear and transparent mesoporous ultra-small silicon nano-solution;
[0014] (3) Loading of drugs on ultra-small silicon nanomaterials:
[0015] The small molecule compound is dissolved in a solvent and slowly added to the mesoporous ultrasmall silicon nano-solution prepared in step (2). After stirring for reaction, the solution is collected and dialyzed with pure water to obtain the light-responsive self-degradable ultrasmall mesoporous organosilicon drug delivery system.
[0016] As a preferred embodiment of the present invention, the carboxyl-containing photosensitizer is one of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin TCPP and photochlorine HPPH; the amide condensation agent is EDCI and / or HOBT; and the silane coupling agent is one of 3-aminopropyltrimethoxysilane APTMS and 3-aminopropyltriethoxysilane APTES.
[0017] As a preferred embodiment of the present invention, step (1) is to weigh a photosensitizer with a carboxyl group and an amide condensation agent into a two-necked bottle, add anhydrous N,N-dimethylformamide, stir and react at 20-30° C. for 40-90 minutes, then add a silane coupling agent, stir and react overnight, monitor the reaction by TLC, and obtain a silanized TCPP preparation solution when the raw materials react completely; wherein the molar ratio of the photosensitizer with a carboxyl group to the silane coupling agent is 1:5.
[0018] As a preferred embodiment of the present invention, the organosilicon source in step (2) is one of bis[3-(trimethoxysilyl)propyl]diselenide and bis[3-(triethoxysilyl)propyl]diselenide BTESePD; the synthesis method of the organosilicon source is:
[0019] Selenium powder, sodium ethoxide and sodium borohydride are reacted in anhydrous ethanol solvent at 0°C with stirring, followed by reflux reaction to generate sodium perselenide, followed by addition of chloropropyltriethoxysilane to the reaction solution to react overnight at room temperature, the reaction is stopped, extraction is performed, spin-dried, and column chromatography is performed to purify to obtain bis[3-(triethoxysilyl)propyl]diselenide (BTESePD);
[0020] Selenium powder, sodium methoxide and sodium borohydride are reacted with stirring at 0°C in anhydrous methanol solvent, followed by reflux reaction to generate sodium perselenide, and then chloropropyltrimethoxysilane is added to the reaction solution to react at room temperature overnight, the reaction is stopped, extraction is performed, spin-dried, and column chromatography is used to purify to obtain bis[3-(trimethoxysilyl)propyl] diselenide.
[0021] As a further preference of the present invention, the synthesis reaction of the organosilicon source is carried out in an organic solvent ethanol / methanol, and the molar ratio of selenium powder to sodium ethoxide / sodium methoxide is 1.1-1.5:1, preferably 1.2:1; the molar ratio of selenium powder to sodium borohydride is 5:1-10:1, preferably 8:1; the molar ratio of selenium powder to chloropropyltriethoxysilane / chloropropyltrimethoxysilane is 1:1-2:1, preferably 1.2:1.
[0022] As a further preferred embodiment of the present invention, the reaction time at 0°C is 0.5 to 2 hours, preferably 0.5 hours; the reflux reaction time is 0.5 to 4 hours, preferably 1 hour; and the overnight reaction time is 8 to 12 hours, preferably 12 hours.
[0023] As a further preferred embodiment of the present invention, the organic solvent used in the extraction is dichloromethane.
[0024] As a further preference of the present invention, the column chromatography is preferably silica gel column chromatography; the solvent of the silica gel column chromatography is preferably petroleum ether (PE): ethyl acetate (EA) = 1:1 to 10:1.
[0025] As a preferred embodiment of the present invention, the alkaline environment described in step (2) is provided by ammonia water with a concentration of 0.01-0.03M; the guiding agent is hexadecyltrimethylammonium bromide CTAB; the inorganic silicon source is one of methyl orthosilicate TMOS and ethyl silicate TEOS, and the molar ratio of the guiding agent to the organic silicon source is 1.5-3:1, preferably 2:1; the molar ratio of the organic silicon source to the silanized photosensitizer is 1:8-15, preferably 1:12.6; the inorganic silicon source and the organic silicon source The molar ratio is 2 to 4:1, preferably 4:1; the PEG chain used to modify the surface of the silica sphere is provided by methoxy polyethylene glycol silane mPEG-Silane, and its molecular weight is preferably 550 to 2000, and the molar ratio of the methoxy polyethylene glycol silane mPEG-Silane to the organic silicon source is 0.8 to 2:1, preferably 2:1; the acidic solution used for dialysis is a mixed solution of ethanol, pure water and acetic acid, and its volume ratio is 1:1:(0.005-0.01), preferably 1:1:0.007. The water used for the second dialysis is preferably ultrapure water; the number of dialysis described above is preferably at least three times.
[0026] As a further preferred embodiment of the present invention, the hydrolysis temperature in step (2) is 25-32°C, preferably 28-30°C.
[0027] As a further preferred embodiment of the present invention, the specific steps in step (2) are as follows: weigh CTAB, dissolve it in an ammonia solution, add the solution into pure water, stir and react at room temperature for 30 minutes until the solution is completely clarified, then slowly drop a mixed solution of TMOS and BTESePD into the above solution, and stir and react at room temperature; then add mPEG-Silane 550 to the reaction solution, and continue to stir and react; increase the reaction temperature to 60-80°C, and stir and react for 20-28 hours; after the reaction, let the reaction solution cool to room temperature, then transfer the reaction solution to a dialysis bag, and dialyze it in a mixed solution of ethanol, pure water and acetic acid for 24 hours, repeating 3-5 times; then, dialyze it in pure water for 24 hours, repeating 3-5 times; finally, filter the solution in the dialysis bag through a 0.22μm filter membrane, and the obtained clear and transparent solution is the desired biodegradable ultra-small organic-inorganic hybrid silicon nanomaterial.
[0028] As a preferred embodiment of the present invention, the solvent in step (3) is one of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF); the small molecule drug is an anti-tumor drug including but not limited to doxorubicin, paclitaxel, and STAT3 inhibitor LLL12.
[0029] As a further preferred embodiment of the present invention, the volume mass ratio of the mesoporous ultrasmall silicon nano-solution and the small molecule drug prepared in step (3) is 1 mL: 2-5 mg.
[0030] As a further preference of the present invention, the reaction temperature of step (3) is 25-32°C, preferably 28-30°C.
[0031] The present invention modifies the surface of the silicon nanoformulation with PEG chains, improves the water solubility and uniformity of the silicon nanoformulation, prolongs the half-life of the preparation in the body, and introduces redox-responsive diselenide bonds to increase the biocompatibility of the material and make it have good biodegradability; in addition, by connecting a photosensitizer to the skeleton of the silicon nanoformulation, the small molecule drugs carried by the nanoformulation can be released on demand at a fixed point in the body under specific laser irradiation conditions, and combined with photodynamic therapy, the level of treatment is improved.
[0032] A light-responsive self-degradable ultrasmall mesoporous organosilicon drug delivery system is prepared according to the preparation method of the present invention.
[0033] The light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system of the present invention is used in preparing drugs for treating tumors.
[0034] Beneficial effects:
[0035] The light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system of the present invention has simple synthesis steps and mild reaction conditions; the particle size of the preparation material is about 10 to 20 nm and the distribution is concentrated, and the preparation has good stability and uniformity; it has low toxicity, good biocompatibility, and a suitable biological half-life, as well as good biodegradability, avoiding the accumulation of silica in the body, etc.; it can also passively target tumor tissues, improve the bioavailability of chemotherapeutic drugs, and release drugs on demand through irradiation with specific laser wavelengths, thereby improving the therapeutic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The characterization results of a biodegradable ultra-small mesoporous organosilicon nanomaterial prepared in the invention, wherein Figure A is a transmission electron microscope image, Figure B is a hydrated particle size image, and Figure C is an elemental energy spectrum analysis image (EDS);
[0037] Figure 2 The characterization results of a light-responsive self-degradable ultra-small mesoporous organosilicon nanomaterial prepared in the invention, wherein Figure A is a transmission electron microscope image, Figure B is a hydrated particle size image, and Figure C is a spectrum of an ultraviolet spectrophotometer;
[0038] Figure 3 The generation of singlet oxygen under laser irradiation in a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system prepared in the invention;
[0039] Figure 4The results of the blood compatibility evaluation of a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system prepared in the invention are shown in Figure A. Figure A is the morphological image of blood cells in each group under the bright field of an inverted microscope; Figure B is the image of each group after incubation with blood cells; Figure C is the hemolytic index of each group;
[0040] Figure 5 The degradation of a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system prepared in the invention under different conditions
[0041] Figure 6 A light-responsive self-degradable ultrasmall mesoporous organosilicon drug delivery system prepared in the invention and the survival rate of 4T1 cells with or without laser irradiation of the nanoformulation encapsulating LLL12. Figure A shows the survival rate of cells with or without light irradiation at different drug concentrations of UMSeN-LLL12, Figure B shows the survival rate of cells with or without light irradiation at different drug concentrations of UMSeN, and Figure C shows the survival rate of cells with or without light irradiation at different drug concentrations of UMSeN and UMSeN-LLL12 under light conditions;
[0042] Figure 7 The production of reactive oxygen species (ROS) at the cell level of a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system prepared in the invention under the conditions of laser irradiation or not, wherein Figure A is the result on the flow cytometer, and Figure B is the result of fluorescence quantification;
[0043] Figure 8 The production of reactive oxygen species (ROS) at the cellular level in a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system prepared in the invention under cell fluorescence imaging with and without laser irradiation, wherein Figure A is the result of cell fluorescence imaging, and Figure B is the result of fluorescence quantification; DETAILED DESCRIPTION
[0044] The following are examples of the present invention, but the following examples do not limit the scope of the present invention.
[0045] Example 1: Preparation of bis[3-(triethoxysilyl)propyl] diselenide (BTESePD)
[0046] Weigh selenium powder (5.00g, 63.32mmol), sodium ethoxide (3.59g, 52.77mmol) in a dry two-necked flask, add 35mL of ethanol solution, and stir to dissolve at 0°C. Then weigh sodium borohydride (0.30g, 7.92mmol) and sodium ethoxide (0.36g, 5.28mmol) and dissolve in 15mL of ethanol solution and slowly drip into the reaction solution, stir at 0°C for 0.5h. Then raise the reaction temperature to 78°C and reflux for 1h. Then add 12.71mL (12.71g, 52.77mmol) of chloropropyltriethoxysilane to the reaction solution and stir at room temperature overnight. The reaction process is monitored by a thin layer plate. After the reaction is completed, add ice water to quench the reaction, filter, collect the filtrate, extract with DCM, and collect the organic phase. Dry with anhydrous sodium sulfate to remove water, spin dry to remove organic solvent, add appropriate amount of 200 mesh silica gel sample preparation column (PE: EA = 10: 1), collect the product and spin dry to obtain orange-yellow oily product BTESePD (11.72 g, 20.61 mmol, yield: 86.79%).
[0047] 1 H NMR(500MHz,Chloroform-d)δ3.82(qd,J=7.0,2.6Hz,12H),3.26-2.90(m,4H),2.00-1.80(m,4H),1.23(td,J=7.0,1.5Hz,18H),0.81-0.71(m,4H);
[0048] 13 C NMR (126MHz, Chloroform-d) δ58.42,33.29,24.25,18.41,10.68;
[0049] HRMS(ESI):exact mass calculated for C 18 H 42 O 6 Se 2 Si 2 m / z 593.0743[M+Na] + ,found:593.0758.
[0050]
[0051] Example 2: Synthesis and characterization of a biodegradable ultra-small mesoporous organosilicon drug delivery system
[0052] 0.2mmol CTAB was weighed and dissolved in 2mL 0.02M ammonia solution. The solution was added into 8mL pure water and stirred at room temperature for 30min until the solution was completely clear. Then, 0.4mmol TMOS and 0.1mmol BTESePD mixed solution (4:1 molar mass ratio) were slowly dripped into the above solution and stirred at 28℃ for 24h. Then, 0.2mmol mPEG-Silane was added to the reaction solution and continued to react at 30℃ for 24h. The reaction temperature was increased to 60℃ and stirred for 24h. After the reaction, the reaction solution was allowed to cool to room temperature and then transferred to a dialysis bag and dialyzed in a mixed solution of 2L ethanol, pure water and acetic acid (1:1:0.007 volume ratio) for 24h, which was repeated three times. Next, the solution was dialyzed in 2L pure water for 24h, which was repeated three times. Finally, the solution in the dialysis bag was filtered through a 0.22μm filter membrane to obtain a clear and transparent solution, which was the desired biodegradable ultrasmall organic-inorganic hybrid silicon nanomaterial and stored at 4℃. 10 μL of silicon nanomaterial solution was dropped onto a copper mesh, dried under an infrared lamp, and the product was detected under a transmission electron microscope. The material morphology results obtained are as follows: Figure 1 -A, as can be seen from the figure, the nanoparticles are round and the material is evenly distributed; the silicon nanomaterial solution is diluted to an appropriate concentration and measured on a hydrated particle size analyzer. The hydrated particle size of the material is 10.50±2.67nm. The results are as follows Figure 1 -B; the element spectrum results of the nanoparticles are as follows Figure 1 As shown in Figure 2, the nanoparticles are mainly composed of two elements, O and Si, and contain 0.9% selenium.
[0053] Example 3: Synthesis and characterization of a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system for photodynamic therapy
[0054] Preparation of silanized TCPP stock solution: Weigh TCPP (20.00 mg, 25.29 μmol), HOBT (17.09 mg, 126.46 μmol), EDCI (24.24 mg, 126.46 μmol) in a dry two-necked bottle, protect with nitrogen, add 2 mL of anhydrous N, N-dimethylformamide to dissolve, stir at room temperature for 1 h. Then add APTMS (22.67 mg, 126.46 μmol), react at room temperature, monitor the reaction progress by TLC, and obtain the silanized TCPP stock solution after the reaction is completed. The stock solution was stored at 4 ° C in the dark for the subsequent preparation and synthesis of ultra-small mesoporous organosilicon nanomaterials that respond to light and self-degrade.
[0055] Synthesis of light-responsive self-degradable ultrasmall mesoporous organosilicon nanomaterials: Weigh 0.2 mmol CTAB and dissolve it in 2 mL 0.02 M ammonia solution. Add the solution to 8 mL pure water and stir at room temperature for 30 min until the solution is completely clear. Then, slowly drop 0.4 mmol TMOS, 0.1 mmol BTESePD mixed solution (4:1 molar mass ratio) and 100 μL of silanized TCPP stock solution (1.26 mmol TCPP) prepared in the previous step into the above solution. Stir the reaction at 28 °C for 24 h. Then, add 0.2 mmol mPEG-Silane 550, continue to react at 30℃ for 24h; increase the reaction temperature to 60℃, stir and react for 24h; after the reaction, let the reaction solution cool to room temperature, then transfer the reaction solution to a dialysis bag, dialyze in a mixed solution of 2L of ethanol, pure water and acetic acid (1:1:0.007 volume ratio) for 24h, repeat three times; next, dialyze in 2L of pure water for 24h, repeat three times; finally, filter the solution in the dialysis bag through a 0.22μm filter membrane, and the obtained clear and transparent solution is the required ultra-small mesoporous organosilicon nanomaterial that can be used for photodynamic therapy and self-degradation, which is stored at 4℃; drop 10μL of the silicon nanomaterial solution on a copper mesh, dry it under an infrared lamp, and detect the product under a transmission electron microscope. The material morphology results obtained are as follows: Figure 2 -A, as can be seen from the figure, the nanoparticles are round and the material is evenly distributed; the silicon nanomaterial solution is diluted to an appropriate concentration and measured on a hydrated particle size analyzer. The hydrated particle size of the material is 17.57±2.71nm. The results are as follows Figure 2 -B; the silicon nanomaterial solution and TCPP were diluted to appropriate concentrations, and the spectrum at 200-700nm was measured on a UV spectrophotometer. The two had the same characteristic absorption peak at 350-700nm, confirming the successful loading of TCPP; the material was used in subsequent experiments.
[0056] Example 4: Drug loading in a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system
[0057] 5 mg of LLL12 was dissolved in 200 μL of DMSO solution, and slowly dripped into 2 mL of the ultrasmall organosilicon nanosolution prepared in Example 2 under stirring. The solution was stirred at room temperature overnight, and the liquid was collected and dialyzed in pure water. The dialyzate collected was the mesoporous silica nanopreparation loaded with LLL12.
[0058] Example 5: Generation of singlet oxygen in a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system under laser irradiation
[0059] 1 mg of 1,3-diphenylisobenzofuran (DPBF) was weighed and dissolved in an ethanol solution to prepare a 1 mM stock solution. The groups were tested according to the experimental groups: pure solvent group (DPBF), free TCPP group (Free TCPP), TCPP-loaded material group (UMSeN-TCPP prepared in Example 2), and blank material group (UMSeN prepared in Example 1). The pure solvent group added an appropriate amount of 1mM DPBF mother solution and anhydrous ethanol to make the DPBF solution concentration of 100μM; the free TCPP group (Free TCPP) added an appropriate amount of 1mM DPBF mother solution and TCPP to anhydrous ethanol to make the TCPP concentration of 10μg / mL and the DPBF solution concentration of 100μM; the TCPP-loaded material group (UMSeN-TCPP) added an appropriate amount of 1mM DPBF mother solution and anhydrous ethanol to make the TCPP concentration of 10μg / mL and the DPBF solution concentration of 100μM, and the material concentration was 1mg / mL; the blank material group (UMSeN) added an appropriate amount of 1mM DPBF mother solution and anhydrous ethanol to make the silicon material UMSeN concentration of 1mg / mL and the DPBF solution concentration of 100μM. After the above samples were prepared, the samples were measured at 660nm (100mW / cm 2 )UV spectra (200-500nm) under near-infrared light irradiation for different times (0, 60, 120, 180, 240, 300, 360, 420, 450, 480, 540, 600, 660, 720s).
[0060] DPBF is a singlet oxygen-indicating fluorescent probe that is sensitive to singlet oxygen ( 1 O 2 ) has high specificity, can form endoperoxides and decompose into 1,2-dibenzoylbenzene. DPBF can be used to detect the generation of reactive oxygen species (ROS). Once combined with singlet oxygen ( 1 O 2 ) combined, DPBF was irreversibly oxidized, and the absorption intensity at UV-visible light (410nm) decreased rapidly. The ability of each group of samples to produce singlet oxygen in vitro was reflected by the percentage of the ratio of the UV absorption intensity of each group of samples at 410nm to the UV absorption intensity at 0s. The results are shown in Figure 3As shown, with the solution containing DPBF and the solution containing UMSeN as the control group, within 720s of laser irradiation, the ultraviolet absorption of DPBF at 410nm only decreased by 11.58%±2.70% compared with 0s; the FreeTCPP group decreased by 46.12%±0.36%; and the UMSeN-TCPP group decreased by 76.21%±2.97%, which is 1.6 times that of the Free TCPP group. The above results show that the ultraviolet absorption of DPBF can be greatly reduced only in the presence of photosensitizers. At the same time, because TCPP is encapsulated on silicon nanoformulations with better dispersibility, UMSeN-TCPP can produce more singlet oxygen than FreeTCPP.
[0061] Example 6: Study on the blood compatibility of a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system
[0062] In order to evaluate the safety of intravenous administration of the material, the ultra-small mesoporous silicon nanoformulation prepared in Example 2 of the invention was studied for blood compatibility. Obtaining blood cells: Collect whole blood from mice, centrifuge at 8000rpm for 5min, discard the supernatant, resuspend the blood cells with saline, then centrifuge at 3500rpm for 7min, resuspend the blood cells with saline, repeat the above operation until the supernatant is clear and transparent, and the blood cells required for blood compatibility study are obtained. Use saline to prepare three concentrations of material solutions of 500μg / mL, 250μg / mL, and 125μg / mL. Take 1mL of 500μg / mL, 250μg / mL, 125μg / mL, pure water, and saline, add 10μL of blood cells, oscillate at 37℃ for 1h, centrifuge at 3500rpm for 7min, take the supernatant to measure the absorbance under 545nm ultraviolet to calculate the hemolytic index. The precipitate is resuspended with saline, and a small amount is dropped on a slide to observe the morphology of blood cells under an inverted microscope. (Pure water was used as the positive control group and saline as the negative control group) Calculation of hemolysis index Z: Z = (absorbance of sample - absorbance of negative control group) / (absorbance of positive control group - absorbance of negative control group) x 100%. The results of the blood compatibility, hemolysis index and cell morphology of ultra-small organic-inorganic hybrid silicon nanomaterials are shown in Figure 2. Figure 4 Shown
[0063] The hemolytic index of the material solution at the three concentrations was less than 5%, indicating that the material had good safety when administered intravenously at 500 μg / mL. In addition, observation of blood cell morphology under an inverted microscope revealed that the morphology of blood cells at these three concentrations was consistent with that of the negative control, showing good cell morphology. The above results all indicate that the nanomaterial has good blood compatibility.
[0064] Example 7: Degradation study of a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system
[0065] Experimental conditions: release speed: 100 rpm; temperature: 37°C ± 0.5°C; release medium: phosphate buffer solution (pH = 7.4), 100 μM H 2 O 2 ; Experimental groups: PBS, 100 μM H 2 O 2 , 100 μM H 2 O 2 +Laser; Sampling time: 0.5h, 1h, 2h, 4h, 6h, 8h, 12h, 24h, 48h
[0066] Experimental process: The degradation experiment of the material was carried out by centrifugation, and the degradation of the UMSeN-TCPP prepared in Example 2 was compared under near-infrared light 660nm (100mW / cm 2 , 15min) and degradation under conditions without light. Add 20mL of release medium solution and 2mL of UMSeN-TCPP solution to a 50mL centrifuge tube, then place the centrifuge tube in a shaker at 37°C, 100rpm, take out 1.5mL of sample at different time points, set the centrifuge parameters to 4°C 15000rpm for 30min, aspirate the supernatant, and add the corresponding volume of release medium solution. After sampling is completed, the content of silicon in each sample is determined by plasma emission spectrometer ICP. The calculation formula for material degradation:
[0067]
[0068] E r : Cumulative degradation of drug; m free : The content of silicon element released by the degradation of silicon material; m drug : The total content of silicon in silicon nanomaterials. The experiment was repeated three times and the average value was taken. The cumulative degradation rate of each sampling point was calculated by the above formula. The degradation curve was drawn using drawing software, with the ordinate being the percentage of material degradation and the abscissa being the sampling time. The results are shown in Figure 5 As shown, in PBS medium, UMSeN-TCPP (prepared in Example 2, the same below) was degraded by only 12.90%±3.20% cumulatively within 168 hours; under redox conditions, the degradation of UMSeN-TCPP was significantly improved, and the degradation rate reached 74.36%±1.23% at 168 hours; and light also increased the degradation rate of UMSeN-TCPP, and the degradation rate reached 94.96%±0.12% at 168 hours. This shows that the ultra-small organosilicon material has good biodegradability and good light-responsive degradation ability.
[0069] Example 8: Evaluation of the anti-tumor activity of a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system in vitro
[0070] 5000 4T1 cells were inoculated in each well of two 96-well plates. After incubation for 24 hours, drugs were administered according to the experimental groups, namely UMSeN (in order to avoid too long a description, the UMSeN-TCPP prepared in Example 2 is abbreviated as UMSeN in this example), UMSeN+Laser, UMSeN-LLL12 (mesoporous silica nanoformulation loaded with LLL12 prepared in Example 3), and UMSeN-LLL12+Laser. The above four groups were diluted in half to 3.125 μg / mL with a maximum concentration of 200 μg / mL, and a series of drugs of different concentrations were added to the 96-well plates. After incubation for 12 hours, UMSeN+Laser and UMSeN-LLL12+Laser were illuminated by a 660nm laser lamp at 100 mw / cm 2 Irradiate for 15 minutes and continue incubation for 12 hours; then add 10 μL of methyl tetrazolium blue (MTT, 5 mg / mL) to each well, incubate in the dark for 4 hours, remove the liquid in the 96-well plate, add 150 μL of DMSO, incubate in the dark with shaking for 15 minutes to fully dissolve the crystals, measure the absorbance of each sample at a wavelength of 570 nm with an enzyme marker, and measure the OD value of the blank group at the same time, and calculate the cell survival rate. The results are shown in Figure 6 .
[0071] The results of the cytotoxicity test showed that the survival rate of 4T1 cells was higher than 90% under the condition of UMSeN concentration of 200 μg / mL without light, while the survival rate of cells was around 20% under light conditions ( Figure 6 B), the results show that the nanomaterial has good safety without light, and has good photodynamic therapy ability; when the concentration of UMSeN-LLL12+Laser is 200μg / mL, the cell survival rate is only about 10%, indicating that the nanomaterial loaded with LLL12 can significantly inhibit the proliferation of tumor cells under light conditions ( Figure 6 A).
[0072] Example 9: Levels of reactive oxygen species produced by 4T1 cells in a photoresponsive self-degrading ultrasmall mesoporous organosilicon drug delivery system with and without laser irradiation
[0073] (1) Flow cytometry to detect reactive oxygen species levels
[0074] 2 x 10 cells were seeded per well of a six-well plate. 54T1 cells were incubated for 24 hours and then the drugs were added according to the experimental groups. The groups were: control group (Control), material group (UMSeN, to avoid too long description, the UMSeN-TCPP prepared in Example 2 is abbreviated as UMSeN in this example), control group plus illumination (Control+Laser), material group plus illumination (UMSeN+Laser). After 6 hours of drug administration, the illumination group was irradiated with a 660nm near-infrared lamp, and the irradiation power was 100mW / cm 2 , irradiation time: 15min. After illumination, continue incubation for 2h, remove the old cell culture medium, and wash three times with pre-cooled phosphate buffer solution; add 1mL of diluted DCFH-DA solution, incubate for a further 20min, and then wash the cells 3 times with phosphate buffer solution to fully remove the DCFH-DA that has not entered the cells; digest the cells with trypsin, wash them, and finally suspend them in phosphate buffer solution. The level of reactive oxygen species generated was quantitatively analyzed by flow cytometry, and FLOWJO software was used for data processing. DCFH-DA was diluted with serum-free culture medium at a ratio of 1:3500 to a final concentration of 3.5μmol / L. The results are as follows Figure 7 As shown, Figure A is the original data of flow cytometry, and Figure B is the quantitative result.
[0075] (2) Cell imaging method to detect reactive oxygen species levels
[0076] Inoculate 1×10 cells per well in a 96-well plate 5 4T1 cells were incubated for 24 hours and then the drugs were added according to the experimental groups. The groups were: control group (Control), material group (UMSeN, to avoid too long description, the UMSeN-TCPP prepared in Example 2 is abbreviated as UMSeN in this example), control group plus illumination (Control+Laser), material group plus illumination (UMSeN+Laser). After 6 hours of drug administration, the illumination group was irradiated with a 660nm near-infrared lamp, and the irradiation power was 100mW / cm 2 , irradiation time: 15min. After illumination, continue incubation for 2h, remove the old cell culture medium, and wash three times with pre-cooled phosphate buffer solution; add 100μL 3.5μmol / L DCFH-DA solution, incubate for further 20min, and then wash the cells 3 times with phosphate buffer solution to fully remove DCFH-DA that has not entered the cells; use ImageXpress Micro 4 (Molecular Devices, CA, USA) to capture the fluorescence image of the cells, fluorescence channels: FITC channel, TL channel. The fluorescence intensity of each group was calculated using imageJ. The results and analyzed data are shown in the figure. Figure 8 As shown;
[0077] Figure 7-Figure 8 The results showed that the fluorescence intensity of the material group plus light was higher than that of the other three groups, indicating that the material can significantly produce reactive oxygen under light conditions at the cellular level and has a good photodynamic therapy effect.
Claims
1. A method for preparing a light-responsive self-degradable ultra-small mesoporous organosilicon drug delivery system, characterized in that: The following steps are involved: (1) Preparation of silanized photosensitizer: A photosensitizer with a carboxyl group undergoes an amidation reaction with a silane coupling agent in the presence of an amide condensation agent to obtain a silanized photosensitizer; (2) Preparation of biodegradable ultra-small silicon nanomaterials for photodynamic therapy: In an alkaline environment, in the presence of a directing agent, the inorganic silicon source, the organic silicon source and the silanized photosensitizer prepared in step (1) are hydrolyzed and cross-linked to form silicon-oxygen bonds, gradually forming silicon spheres, and PEG chains are modified on the surface thereof to increase the stability of the preparation. The reaction solution is dialyzed with an acidic solution and water, and filtered with a 0.22 μm filter membrane to obtain a clear and transparent mesoporous ultra-small silicon nano-solution; (3) Loading of drugs on ultra-small silicon nanomaterials: The small molecule compound is dissolved in a solvent and slowly added to the mesoporous ultrasmall silicon nano-solution prepared in step (2). After stirring for reaction, the solution is collected and dialyzed with pure water to obtain the light-responsive self-degradable ultrasmall mesoporous organosilicon drug delivery system.
2. The preparation method according to claim 1, characterized in that: The carboxyl-containing photosensitizer described in step (1) is one of 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin TCPP and photochlorine HPPH; the amide condensation agent is EDCI and / or HOBT; and the silane coupling agent is one of 3-aminopropyltrimethoxysilane APTMS and 3-aminopropyltriethoxysilane APTES.
3. The preparation method according to claim 1, characterized in that: The step (1) is to weigh a photosensitizer with a carboxyl group and an amide condensation agent into a two-necked bottle, add anhydrous dimethyl sulfoxide, stir and react at 20-30° C. for 40-90 minutes, then add a silane coupling agent, stir and react overnight, monitor the reaction by TLC, and obtain a silanized TCPP preparation solution when the raw materials react completely; wherein the molar ratio of the photosensitizer with a carboxyl group to the silane coupling agent is 1:
5.
4. The preparation method according to claim 1, characterized in that: The organosilicon source in step (2) is selected from one of bis[3-(trimethoxysilyl)propyl]diselenide and bis[3-(triethoxysilyl)propyl]diselenide BTESePD; the organosilicon source is prepared by the following method: Selenium powder, sodium ethoxide and sodium borohydride are reacted in anhydrous ethanol solvent at 0°C with stirring, followed by reflux reaction to generate sodium perselenide, followed by addition of chloropropyltriethoxysilane to the reaction solution to react overnight at room temperature, the reaction is stopped, extraction is performed, spin-dried, and column chromatography is performed to purify to obtain bis[3-(triethoxysilyl)propyl]diselenide; Alternatively, selenium powder is reacted with sodium methoxide and sodium borohydride in anhydrous methanol solvent at 0° C. with stirring, followed by reflux reaction to generate sodium perselenide, and then chloropropyltrimethoxysilane is added to the reaction solution to react at room temperature overnight, the reaction is stopped, extraction is performed, spin-dried, and column chromatography is used for purification to obtain bis[3-(trimethoxysilyl)propyl]diselenide.
5. The preparation method according to claim 4, characterized in that: The molar ratio of selenium powder to sodium ethoxide / sodium methoxide is 1.1-1.5:1, preferably 1.2:1; the molar ratio of selenium powder to sodium borohydride is 5:1-10:1, preferably 8:1; the molar ratio of selenium powder to chloropropyltriethoxysilane / chloropropyltrimethoxysilane is 1:1-2:1, preferably 1.2:1; the reaction time at 0°C is 0.5-2h, preferably 0.5h; the reflux reaction time is 0.5-4h, preferably 1h; the reaction time of overnight reaction is 8-12h, preferably 12h; the organic solvent used in the extraction is dichloromethane; the column chromatography is silica gel column chromatography; the solvent of the silica gel column chromatography is preferably petroleum ether (PE): ethyl acetate (EA) = 1:1-10:
1.
6. The preparation method according to claim 1, characterized in that: The alkaline environment described in step (2) is provided by ammonia water with a concentration of 0.01-0.03M; the guiding agent is hexadecyltrimethylammonium bromide CTAB; the inorganic silicon source is one of methyl orthosilicate TMOS and ethyl silicate TEOS, the molar ratio of the guiding agent to the organic silicon source is 1.5-3:1, the molar ratio of the organic silicon source to the silanized photosensitizer is 1:8-15, and the molar mass ratio of the inorganic silicon source to the organic silicon source is 2-4:1; used for modifying The PEG chain on the surface of the silica sphere is provided by methoxy polyethylene glycol silane mPEG-Silane, and its molecular weight is preferably 550-2000, and the molar weight of the methoxy polyethylene glycol silane mPEG-Silane and the organic silicon source is 0.8-2:1; the acidic solution used for dialysis is a mixed solution of ethanol, pure water and acetic acid, and the volume ratio is 1:1:(0.005-0.01); the hydrolysis temperature is preferably 25-32°C, and more preferably 28-30°C.
7. The preparation method according to claim 6, characterized in that: The specific steps in step (2) are as follows: weigh CTAB, dissolve it in an ammonia solution, add the solution into pure water, stir and react at room temperature for 30 minutes until the solution is completely clear, then slowly drop a mixed solution of TMOS and BTESePD into the above solution, and stir and react at room temperature; then add mPEG-Silane550 to the reaction solution, and continue to stir and react; increase the reaction temperature to 60-80°C, and stir and react for 20-28 hours; after the reaction is completed, let the reaction solution cool to room temperature, then transfer the reaction solution to a dialysis bag, and dialyze it in a mixed solution of ethanol, pure water and acetic acid for 24 hours, repeating 3-5 times; then, dialyze it in pure water for 24 hours, repeating 3-5 times; finally, filter the solution in the dialysis bag through a 0.22μm filter membrane, and the obtained clear and transparent solution is the desired biodegradable ultra-small organic-inorganic hybrid silicon nanomaterial.
8. The preparation method according to claim 7, characterized in that: The solvent described in step (3) is one of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF); the small molecule drug is an anti-tumor drug including but not limited to doxorubicin, paclitaxel, and STAT3 inhibitor LLL12; the reaction temperature of step (3) is 25-32°C, preferably 28-30°C. 9 . The light-responsive self-degrading ultrasmall mesoporous organosilicon drug delivery system prepared according to the preparation method of any one of claims 1 to 8 .
10. Use of the light-responsive self-degrading ultrasmall mesoporous organosilicon drug delivery system according to claim 9 in the preparation of drugs for treating tumors.